+0  
 
+5
93
1
avatar+359 

Let f(x) = 2x - 3 and g(f(x)) = 5-4x. Find g(4).

coolcoolcool

MIRB16  Jul 22, 2017
edited by Guest  Jul 22, 2017
edited by Guest  Jul 22, 2017
Sort: 

1+0 Answers

 #1
avatar+4728 
+1

g( f(x) )  =  5 - 4x

 

We want to find  g(4)  , that is, we want to find  g  when...

 

f(x)  =  4

                             Since  f(x)  =  2x - 3  , we can replace  f(x)  with  2x - 3  .

2x - 3  =  4

                             Add  3  to both sides.

2x  =  7

                             Divide both sides by  2  .

x  =  7/2

 

Now we know that when  x = 7/2  , f(x)  =  4 .

 

g( f(x) )  =  5 - 4x

                                              Replace every instance of  x  with  7/2  .

g( (f(7/2) )  =  5 - 4(7/2)

                                              Since  f(7/2)  =  4 , we can say...

g(4)  =  5 - 4(7/2)

 

g(4)  =  -9

hectictar  Jul 22, 2017

5 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details